Differentiated approach in diagnostics, diagnosis formulation, case management and statistical accounting of type 2 myocardial infarction (Position Paper) - O. V. Averkov; O. L. Barbarash; S. A. Boytsov; E. Yu. Vasilieva; O. M. Drapkina; A. S. Galyavich; M. Yu. Gilyarov; O. V. Zayratiants; L. V. Kakturskiy; Yu. A. Karpov; O. D. Mishnev; N. N. Nikulina; et al. (Российский кардиологический журнал)
.